2015
DOI: 10.1111/ffe.12348
|View full text |Cite
|
Sign up to set email alerts
|

Very high cycle fatigue crack initiation mechanism according to a 3D model of persistent slip bands formation in α‐ferrite

Abstract: A B S T R A C T Many studies on the behaviour of very high cycle fatigue (VHCF) showed that there appear some distinguishable features compared with the low and high cycle fatigue. The understanding of mechanism of fatigue crack initiation in VHCF is very important.In the present work, 1 mm thin sheet specimens on commercial pure iron were employed to perform tests under tension-compression cyclic loading at 20 kHz ultrasonic frequency. In situ observation was carried out with thermal and optical imaging. Loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Slightly decreasing the stress amplitude will need a much larger area of initiation because of the square relationship and certainty of ∆K th . Irreversible slip bands at the initiation site form very slowly in the VHCF regime and are strongly dependent on microstructure characteristics, leading to a progressively weaker area with discrete nanoscale damage. Accordingly, the slope of the S‐N curve is lower.…”
Section: Resultsmentioning
confidence: 99%
“…Slightly decreasing the stress amplitude will need a much larger area of initiation because of the square relationship and certainty of ∆K th . Irreversible slip bands at the initiation site form very slowly in the VHCF regime and are strongly dependent on microstructure characteristics, leading to a progressively weaker area with discrete nanoscale damage. Accordingly, the slope of the S‐N curve is lower.…”
Section: Resultsmentioning
confidence: 99%
“…Observations at the specimen surface were made during the tests (for 3 tests) by light microscope. These observations showed that irreversible slip bands (PSBs) were formed at the beginning of the fatigue loading [1,21]. These slip bands multiplied or grew within the same grain during subsequent cycle loading.…”
Section: Observation Of Psbs At the Specimen Surfacementioning
confidence: 99%
“…A specimen showing pronounced PSBs on three perpendicular surfaces, Fig. 3a, was investigated by SEM to gain a 3D understanding of mechanism of PSB formation [21]. The axial and cross surfaces were mechanically polished and etched with 4% Nital.…”
Section: Psb Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this paper is to investigate the qualitative correlation between the dissipated energy and the slip markings for the three materials of interest during fatigue tests conducted at 20 kHz using an ultrasonic device and to compare the material responses. Some results obtained on copper and a-iron have been published [10][11][12][13][14][15]. These results are summarized and completed in order to compare the fracture, thermal and microstructural responses in VHCF.…”
Section: Introductionmentioning
confidence: 99%